1999
DOI: 10.1152/ajpgi.1999.276.2.g431
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of59Fe movement across the intestinal wall in duodenal rat segments ex vivo

Abstract: Duodenal segments from iron-deficient and iron-adequate rats were luminally perfused ex vivo with solutions containing 1, 10, 50, 100, 200 and 500 μmol59Fe/l. When duodenal tissue load and mucosal-to-serosal transport had reached a steady state, perfusion was continued without luminal 59Fe supply. Mobilization of 59Fe from the duodenal tissue into the serosally released absorbate followed first-order rate kinetics, which permitted calculation of the asymptotic maximum, the rate constant, and the initial mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…This is in agreement with previous kinetic findings on the adaptation of uptake and transfer in iron-deficient rats, where the fraction of iron available for transfer across the basolateral membrane increased in parallel to the available fraction of iron when "uptake" and "transfer" are in a steady state. 17 It cannot however, be ruled out that the decreased transfer of iron is due to a coordinated decrease in the iron absorption pathway. The latter possibility is consistent with the observations of Frazer et al 9 in iron-deficient rats.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous kinetic findings on the adaptation of uptake and transfer in iron-deficient rats, where the fraction of iron available for transfer across the basolateral membrane increased in parallel to the available fraction of iron when "uptake" and "transfer" are in a steady state. 17 It cannot however, be ruled out that the decreased transfer of iron is due to a coordinated decrease in the iron absorption pathway. The latter possibility is consistent with the observations of Frazer et al 9 in iron-deficient rats.…”
Section: Discussionmentioning
confidence: 99%
“…3317, Merck). Plasma transferrin was measured by immunodiffusion technique as described (17). For conversion to total iron binding capacity (micrograms of Fe͞100 ml), plasma transferrin concentrations (milligrams of protein͞milliliter) were multiplied by 140, assuming a molecular mass of 80 and 56 Da for transferrin and iron, respectively (18).…”
Section: Methodsmentioning
confidence: 99%
“…3. Within the thymus, the number and percent of the four major populations, double negative (CD4 absorption is geared to the demand (12,13,17). As the digestive tract carries a unique population of intraepithelial lymphocytes (IELs), mainly T cells (29), alterations in these populations could have been possible in HFE o͞o mice, a prospect not previously explored (16).…”
Section: Table 4 Irp-1 Activity In Duodenal Mucosamentioning
confidence: 99%
“…A previous study [28] revealed that the initial 59 Fe release rate in the kinetics of 59 Fe transfer from the duodenal segment is strongly correlated with basolateral 59 Fe release from mucosal enterocytes, irrespective of the mucosal 59 Fe load or the body iron status. Therefore, first-order rate kinetics were fitted to the cumulative 59 Fe release data using nonlinear regression analysis, and the asymptotic maximum was multiplied by the rate constant to calculate the initial 59 Fe release rate.…”
Section: Effects Of Duration Of Swimming Exercise On Basolateral Ironmentioning
confidence: 93%
“…The duodenal segment was luminally perfused ex vivo, as previously described [28]. Briefly, the perfusion conditions were as follows: recirculating luminal perfusion with 30 ml of the perfusion solution (37°C), which was equilibrated with 95% O 2 /5% CO 2 , 25 cmH 2 O hydrostatic pressure, and 50 ml/min flow rate.…”
Section: Iron Transfer Kineticsmentioning
confidence: 99%